Complexing daunorubicin with β-cyclodextrin derivative increases drug intercalation into DNA. (1st September 2017) - Krzak, Agata; Swiech, Olga; Majdecki, Maciej; Bilewicz, Renata
Abstract: A non-toxic lipoic acid derivative of β-cyclodextrin (βCDLip) with an electron-rich aromatic linker was studied as a carrier for the drug daunorubicin with the aim of increasing the intercalation efficiency of the drug into the double stranded DNA. The impact of cyclodextrins modified with lipoic acid on the interaction of daunorubicin with dsDNA was investigated by UV–vis spectroscopy and square wave voltammetry, and described using the McGhee and von Hippel model. The changes of the stability constants of the complexes reveal the dependence of drug binding efficiency on pH and explain the observed changes in the extent of drug intercalation into dsDNA.